The Potential of the Motor Vehicle Tax (PKB) Opsen in Increasing Regional Original Revenue (PAD) in Bengkalis Regency - Nurul Rauda; Novira Sartika (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the implementation of the Motor Vehicle Tax (PKB) Opsen to increase Regional Original Revenue (PAD) in Bengkalis Regency following the enactment of Law Number 1 of 2022 on Financial Relations between the Central Government and Regional Governments (HKPD Law). The research examines the development of PAD and PKB revenue prior to the PKB Opsen, assesses the potential contribution of PKB Opsen to PAD after its implementation in 2025, and identifies obstacles and efforts undertaken by the Regional Revenue Agency (Bapenda) and the Bengkalis Revenue Management Unit (UPT SAMSAT). This study employs a Qualitative approach using primary data from interviews and observations, as well as secondary data from official documents and revenue reports. The findings indicate that the PKB Opsen policy provides new fiscal space for Bengkalis Regency and contributes positively to PAD without increasing the tax burden on taxpayers. However, its implementation still faces challenges, including administrative constraints, information system limitations, taxpayer compliance issues, and limited public understanding. To address these challenges, Bapenda and UPT SAMSAT have strengthened coordination, improved administrative systems, and intensified public outreach. Overall, the PKB Opsen has significant potential to strengthen regional fiscal independence and reduce reliance on central government transfers if implemented effectively.